Controle de Alphitobius diaperinus (Panzer) (Coleoptera: Tenebrionidae) em instalações para frangos de corte - Souza, L. M.; Silva, G. S.; Belo, M. A A; Soares, V. E.; Costa, A. J. [UNESP] (My University, 2009)
Searching for a new alternative to A. diaperinus control, it was evaluated the action of Spinosad in two concentrations (250ppm, 400ppm) and two doses (0.05 L/m 2 and 0.1 L/m 2), applied in poultry broiler facilities naturally infested by this coleoptera. Assessments of the infestation were held in weekly intervals, during 49 days after treatment, using traps. The percentage of effectiveness were calculated from the results of the number of adults and/or larval stages in control and treated groups. Spinosad at the concentration of 250ppm, applied at a dose of 0.1L/m2, can be considered ineffective against these beetles, however the application of 400ppm at a dose of 0.1L/m2 showed high efficacy and short residual period. The dose of 0.1L/m 22 of Spinosad at the concentration of 400ppm demonstrated, between treatments, better effectiveness against coleopters, reaching efficacy of 100% against larvae of A. diaperinus, observed after the seventh day post-treatment.
Control of Alphitobius diaperinus (Panzer) (Coleoptera: Tenebrionidae) in broiler facilities
Keywords: Beetles; Efficacy; Poultry; Sacharopolyspora spinosa; Spinosad; Alphitobius diaperinus; Coleoptera; Tenebrionidae